Understanding Narcissism in the Workplace: The Dual Impact of Self-Efficacy and Political Skill on Attitudes and Performance - Davis, Maggie M.; Howard, Matt C. (Journal of Organizational Psychology, 2024)
This study examines cognitive and behavioral mechanisms that explain why narcissism leads to positive and negative workplace outcomes. By sampling 296 working adults in the United States at three time points, we tested the model using partial least squares structural equation modeling. Drawing from social cognitive theory, we explore how grandiose and vulnerable narcissism influence workplace attitudes and behaviors, including organizational commitment, citizenship behavior, and workplace deviance. Our findings reveal that these differences are mediated through the serial mechanisms of self-efficacy and political skill. By highlighting the role of self-concept and social effectiveness skills in shaping narcissistic employees’ workplace behaviors, this study contributes to a deeper theoretical understanding of the factors motivating their engagement in positive workplace contributions versus unethical workplace behaviors.